Meaning and aging: humanist perspectives - Duyndam, Joachim; Machielse, Anja (Studies in humanism and atheism, 2024)
The main objective of this book is to add, from a humanist perspective, new interdisciplinary insights and research results to the current academic debate on aging. The collection aims to enhance and complement the predominantly biomedical and sociological debates and provide a more comprehensive and highly topical view on aging and old age. By purveying a meaning-in-life perspective to the current debate we want to enrich and to deepen the research on aging, thus aspiring to an ideal of meaningful aging. The starting point of this book is a humanistic meaning frame for addressing basic needs of a meaningful existence, such as having goals in life, a sense of self-worth, connectedness with others, moral justification, a certain degree of understanding (comprehensibility), direction and influence with a view to cohesion in life, and not in the least place: (living) pleasure or excitement. Taken together, the essays show that experiencing a meaningful life contributes to one's mentalresilience, conceived as the ability to realize a humane individuality (autonomy) in thinking and acting in situations of adversity and vulnerability, particularly those faced by older people